Portrayal of the Contemporary African Politician in Swahili Poetry - Kinoti, Timothy M.; Mwenda, Mukuthuria; Kobia, John M. (My University, 2015)
This study was, in a broader sense, intended to identify the many political, social and economic changes that the continent of Africa has undergone since independence. Among the significant changes witnessed are those of its political leaders. This study analyzed the various traits and actions of Africa’s contemporary political leaders as portrayed by Kiswahili poets. The objective of this study was to evaluate the changes that the contemporary African politician has undergone since the attainment of multiparty democracy according to swahili poets. The study was guided by post-colonial Theory which is associated with the works of Edward W. Said, Gayatri Chakravorty Spivak and Homi K. Bhabha. Data was collected from selected onthologies of Kiswahili poems using purposive sampling method. Qualitative analysis of the selected poems was done guided by the research objective. The findings of the study revealed that although the African continent has made remarkable steps in enhancing democracy, a good number of its political leaders, whom were credited for championing multiparty democracy, have turned out to be tormentors of the very people they had sworn to protect
Keywords: Contemporary African politician; Swahili poetry; Multi-party democracy